ANALISIS SANITASI KANDANG AYAM DAN KEPADATAN LALAT DI DESA NAMORIH DUSUN II KECAMATAN PANCUR BATU TAHUN 2023 - Siagian, David; Bukit, Yeheskiel (Akupun Tour Publisher, 2024)
Background: Broiler chicken farming business according to the Regulation of the Minister of Agriculture of the Republic of Indonesia No. 31/Permentan/140/2/2014, broiler chicken cultivation needs to be further developed to increase the income and welfare of breeders, livestock companies and the community, including increasing competitiveness. The large number of farms standing in residential areas can have an adverse impact on public health if the management of the farms does not comply with applicable regulations. Farmers still ignore environmental problems, so many people complain about the existence of these livestock businesses. Apart from causing environmental pollution impacts such as air pollution (odor), there are many flies hanging around the cage and the surrounding environment. Purpose: To determine the Analysis Of Chickenhood Sanitation And Late Density In Namorih Village Dusun Ii Kecamatan Pancur Batu. Method: The type of research used was descriptive which aimed to describe the sanitation of chicken coops and the level of fly density in Namorih Dusun II Village, Pancur Batu District, Deli Serdang Regency. The population of this research were 5 broiler chicken breeders in Namorih Dusun II Village, Pancur Batu District, Deli Serdang Regency and a sample of 5 breeders was taken using total sampling technique. The data collection method is direct observation using a questionnaire. Data were processed using univariate analysis Disscusion and Conclusion: The research results showed that of the 5 chicken coops that were observed, there were 3 (60%) chicken coops with good sanitation and 2 (40%) chicken coops with moderate sanitation. Of the 5 chicken coops observed, there were 4 (80%) chicken coops with medium fly densities and 1 (20%) chicken coops with high fly densities. It is hoped that broiler chicken breeders will improve sanitation facilities both in broiler chicken coops and the surrounding environment and control them.